Menggagas Pendidikan Entrepreneur dan Perempuan Mandiri - Suprihatin, Sri Emy Yuli (Musawa Jurnal Studi Gender dan Islam, 2008)
It is the time for Indonesian women to become autonomous women. This contention has a substantial reason. In fact, many husbands or fathers, who are considered the breadwinners of family, cannot provide an adequate income to fulfill their family needs. Many women have also become single parents because of getting divorce or their husbands or fathers died. How should women struggle with these mentioned conditions? How could they fulfill their individual and family needs if they do not know how to deal with the problems? How could women sustain their own and family life if they are physically and intellectually weak, poor and do not know what to do? The phenomena indicate the urgency of giving women an entrepreneurship education that will assist them to live independently and be capable of maintaining their life and family survival.